KONSERVASI PIPER MINIATUM Bl. DENGAN PERBANYAKAN CARA PERUNDUKAN;EKSTRAKSI DAN UJI AKTIFITAS ANTIRADIKAL BEBAS DPPH, DAN ANTIDIABETIK - Sumarnie Hasto Priyono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
The aim of this study was to determine the potency of Piper miniatum as medicinal plant and its propagation method. Extraction and bioassays test (antioxidant activity by DPPH method and antidiabetes by á- glucocidase test) were done. Propagationwas done by bending the internodes at different maturity (R1, R2, R3) and growth medium (compost artificial, mixed husk, forest compost and soil as control treatment).The experimental design in this study was Complete Block Design, with 10 replication. The result showed that forest compost had positive respons to numberof shoot, number of new internodes, and number of leaves on R1, R2 and R3. Old internode showed positive effect at mixed husk growth medium to number of shoots (19), emergence of new internodes (21). New seedling/plantlet were obtained 4 weeksearlier at bending treatment than that of stem cutting. Bioassays test showed that methanol extract of P. miniatum had no- free radical scavenger activity but very active on á-glukocidase inhibition with LC50 for leaves and mixed of leaves and stem were 0.82 and10.75 respectively.